Motor Control and Perception during Haptic Sensing: Effects of Varying Attentional Demand, Stimuli and Age - Master, Sabah (Université d'Ottawa / University of Ottawa, 2012)
This thesis describes a series of experiments in human observers using neurophysiological and behavioural approaches to investigate the effects of varying haptic stimuli, attentional demand and age on motor control and perception during haptic sensing (i.e., using the hand to seek sensory information by touch). In Experiments I-IV, transcranial magnetic stimulation (TMS) was used to explore changes in corticomotor excitability when participants were actively engaged in haptic sensing tasks. These studies showed that corticospinal excitability, as reflected in motor evoked potential (MEP) amplitude, was greatly enhanced when participants were engaged in different forms of haptic sensing. Interestingly, this extra corticomotor facilitation was absent when participants performed finger movements without haptic sensing or when attention was diverted away from haptic input by a concurrent cognitive task (Exp I). This provided strong evidence that the observed corticomotor facilitation was likely central in origin and related to haptic attention. Neuroimaging has shown activation of the parieto-frontal network likely subserves this aspect of haptic perception. Further, this haptic-specific corticomotor facilitation was finely modulated depending on whether participants focused attention on identifying material (texture) as opposed to geometric properties of scanned surfaces (Exp II). With regards to aging effects, haptic-related corticomotor facilitation was associated with higher recognition accuracy in seniors (Exp III). In line with this, seniors exhibited similar levels of haptic-related corticomotor facilitation to young adults when task demands were adjusted for age (Exp IV). Interestingly, both young and senior adults also showed substantial corticomotor facilitation in the ‘resting’ hand when the ipsilateral hand was engaged in haptic sensing (Exp IV). Simply touching the stimulus without being required to identify its properties (no attentional task demands) produced no extra corticomotor facilitation in either hand or age group, attesting again to the specificity of the effects with regards to haptic attention. In Experiments V-VI, the ability to recognise 2-D letters by touch was investigated using kinematic and psychophysical measures. In Experiment V, we characterized how age affected contact forces deployed at the fingertip. This investigation showed that older adults exhibited lower normal force and increased letter-to-letter variability in normal force when compared to young adults. This difference in contact force likely contributed to longer contact times and lower recognition accuracy in older adults, suggesting a central contribution to age-related declines in haptic perception. Consistent with this interpretation, Experiment VI showed that haptic letter recognition in older adults was characterized not only by lower recognition accuracy but also by substantial increases in response times and specific patterns of confusion between letters. All in all, these investigations highlight the critical interaction of central factors such as attentional demand with aging effects on motor and perceptual aspects of haptic sensing. Of particular significance is the clear demonstration that corticomotor excitability is greatly enhanced when a haptic sensing component (i.e., attending to specific haptic features) is added to simple finger movements performed at minimal voluntary effort levels (typically <15 % of the maximal effort). These observations underline the therapeutic potential of active sensory training strategies based on haptic sensing tasks for the re-education of motor and perceptual deficits in hand function (e.g., subsequent to a stroke). The importance of adjusting attentional demands and stimuli is highlighted, particularly with regards to special considerations in the aging population.
Keywords: haptic; tms; transcranial magnetic stimulation; sensing; aging; perception; motor control; attention; touch; tactile; discrimination; corticospinal; excitability; motor cortex; hand